Trace Fossils from the Brioverian (Ediacaran–Fortunian) in Brittany (NW France). Issue 1 (2nd January 2018) - Gougeon, Romain; Néraudeau, Didier; Dabard, Marie-Pierre; Pierson-Wickmann, Anne-Catherine; Polette, France; Poujol, Marc; Saint-Martin, Jean-Paul
ABSTRACT: The Ediacaran–Fortunian ichnofauna from Central Brittany (NW France) is revised for the first time since the pioneering work by Lebesconte at the end of the 19th century. The study is based on fossils from the type-localities of the historical Brioverian taxa Montfortia (traces from Montfort-sur-Meu) and Neantia (wrinkle surfaces from Néant-sur-Yvel), and on two new outcrops from Saint-Gonlay. The ichnofossil assemblage includes Helminthoidichnites tenuis, Helminthopsis tenuis, Gordia marina, Palaeophycus tubularis, ?Neonereites uniserialis, and ?Spirodesmos archimedeus . Locally, the grazing traces are associated with wrinkle surfaces considered as microbially induced sedimentary structures (MISS). The sedimentological characteristics of these deposits correspond to a shelf marine environment. Both U-Pb datings on detrital zircon and ichnostratigraphic criteria tend toward an Ediacaran age of the fossiliferous deposits, but we cannot exclude the possibility of a Fortunian age at the present state of knowledge.